CXCL12 mediates glioblastoma resistance to radiotherapy in the subventricular zone. Issue 1 (1st July 2016) - Goffart, Nicolas; Lombard, Arnaud; Lallemand, François; Kroonen, Jérôme; Nassen, Jessica; Di Valentin, Emmanuel; Berendsen, Sharon; Dedobbeleer, Matthias; Willems, Estelle; Robe, Pierre; Bours, Vincent; Martin, Didier; et al.
Abstract: Background: Patients with glioblastoma (GBM) have an overall median survival of 15 months despite multimodal therapy. These catastrophic survival rates are to be correlated to systematic relapses that might arise from remaining glioblastoma stem cells (GSCs) left behind after surgery. In this line, it has recently been demonstrated that GSCs are able to escape the tumor mass and preferentially colonize the adult subventricular zone (SVZ). At a distance from the initial tumor site, these GSCs might therefore represent a high-quality model of clinical resilience to therapy and cancer relapses as they specifically retain tumor-initiating abilities. Method: While relying on recent findings that have validated the existence of GSCs in the human SVZ, we questioned the role of the SVZ niche as a potential GSC reservoir involved in therapeutic failure. Results: Our results demonstrate that (i) GSCs located in the SVZ are specifically resistant to radiation in vivo, (ii) these cells display enhanced mesenchymal roots that are known to be associated with cancer radioresistance, (iii) these mesenchymal traits are specifically upregulated by CXCL12 (stromal cell-derived factor-1) both in vitro and in the SVZ environment, (iv) the amount of SVZ-released CXCL12 mediates GBM resistance to radiation in vitro, and (v) interferes with the CXCL12/CXCR4 signalling system, allowing weakening of the tumor mesenchymal roots and radiosensitizing SVZ-nested GBM cells. Conclusion: Together, these data provide evidence on how the adult SVZ environment, through the release of CXCL12, supports GBM therapeutic failure and potential tumor relapse.